2021
DOI: 10.7759/cureus.13965
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Depression and Insomnia in Community-Dwelling Elderly People: A Cross-Sectional Evidence of Their Bidirectional Relationship

Abstract: The aim of this study was to examine associated factors of depression and insomnia in community-dwelling elderly people in order to identify independent predictors. Materials and methods A cross-sectional study was conducted among 250 older people aged 60 years and over living in an urban area. A stratified random sampling method was used for recruiting samples from five Open Care Centers for Elderly People of the Municipality of Larissa, Greece. Data were obtained through a questionnaire that included demogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
3
2
0
1
Order By: Relevance
“…According to our results, 22.5% of the sample experienced moderate depression, 5.5% experienced severe depression, 40.5% experienced insomnia, and 19% experienced comorbid depression and insomnia. These results are in accordance with previous studies conducted in Greece, in which the prevalence of moderate depression was found to be 22%, that of severe depression was 6.4%, and that of insomnia was 39.2% [ 6 ]. In a recent meta-analysis of 42 studies considering 57,486 adults, the average expected prevalence of depression among the elderly was found to be 31.74% [ 23 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…According to our results, 22.5% of the sample experienced moderate depression, 5.5% experienced severe depression, 40.5% experienced insomnia, and 19% experienced comorbid depression and insomnia. These results are in accordance with previous studies conducted in Greece, in which the prevalence of moderate depression was found to be 22%, that of severe depression was 6.4%, and that of insomnia was 39.2% [ 6 ]. In a recent meta-analysis of 42 studies considering 57,486 adults, the average expected prevalence of depression among the elderly was found to be 31.74% [ 23 ].…”
Section: Discussionsupporting
confidence: 93%
“…According to research, various factors can mediate or moderate the link between depression and insomnia, including socio-demographic characteristics (such age, gender, and social support), and a number of neurobiological factors (such as stress) may mediate/moderate the insomnia–depression link [ 25 , 26 ]. The prevalence of comorbid depression and insomnia was found to be 19%, and this finding is consistent with previous studies that indicated a bidirectional relationship between those two conditions [ 6 , 15 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Đối với ung thư vú, một số nghiên cứu tổng quan hệ thống trước đây cho thấy tỷ lệ lo âu và trầm cảm ở người bệnh lần lượt là 41,9% và 32,2% (Hashemi và cộng sự, 2020; Pilevarzadeh và cộng sự, 2019) 2, 3 . Một nghiên cứu khác tại Hy Lạp năm 2018 cũng báo cáo một tỷ lệ lớn người bệnh ung thư vú được phân loại là trầm cảm (38,2%) và lo âu (32,2%) 4 . Sự lo âu, sợ hãi có thể làm cho việc đối mặt với điều trị ung thư trở nên khó khăn, cũng làm người bệnh khó đưa ra các quyết định liên quan tới điều trị và chăm sóc 5 .…”
Section: đặT Vấn đềunclassified